Delayed replantation of an avulsed maxillary premolar with open apex: A 24 months follow-up case report - K S Ravi; C Pinky; Shikhar Kumar; Amit Vanka (Wolters Kluwer Medknow Publications, 2013)
Avulsion of permanent teeth is most serious of all dental injuries and accounts for 1-16% of all traumatic injuries, of which maxillary incisors are most commonly involved. However, in this report a rare case of isolated avulsed immature premolar has been described. The patient had reported more than 3 hours after the trauma with a tooth stored in dry condition and soil contamination. The prognosis depends on measures taken at the place of accident or the time immediately after avulsion. Replantation is the treatment of choice, but cannot always be performed immediately. An appropriate emergency management and treatment plan is important for good prognosis. In this report stepwise management of an avulsed immature maxillary premolar with extended period of dry storage has been described followed up for a period of 2 yrs.